PENGATURAN HAK MENYUSUI ANAK PADA WAKTU KERJA DALAM HUKUM KETENAGAKERJAAN - Elza Qorina Pangestika (Universitas Slamet Riyadi, 2018)
The purpose of this writing is to find suitability of breast-feeding rights regulated in Act No. 13 of 2003 on Labour with the philosophy of woman’s reproductive rights. This writing is a writing normative laws. This writing is done by means of literature study to obtain secondary data in the field of law. From the result of study it can be concluded that first, in general provisions concerning of breast-feeding rights in Act No. 13 of 2003 on Labour was already conformed the philosophy of woman’s reproductive rights. Second, in specifically provisions concerning of breast-feeding rights in Article 83 of Act No. 13 of 2003 on Labour still has not been entirely conformed with the philosophy of woman’s reproductive rights, because it has not guaranteed full rights to female workers who breastfeed their babies.